The Green Legacy of 1989: Revolutions, Environmentalism and the Global Age. (20th May 2013) - Corry, Olaf
<x xml:space="preserve">Abstract</x> In its immediate aftermath the Eastern European revolutions of 1989–91 were interpreted as a 'rectifying revolution': the experiment of 1917 had been cast off but the process bequeathed no new ideas. Subsequent debates linked 1989 to novel political methods and a re‐launch of 'civil society' but failed to note the significance of dissident and protest movements which relied on environmentalist critiques of industrialism, materialism and top‐down government. The article first points to three phases of debate about the legacy of 1989 noting the relative neglect of environmentalism in all of them. Second, it charts the centrality of environmentalist ideas to the early dissidents, the revolutionary movements that mobilised and to the global social movements that have emerged since 1989. The final section argues that this 'green 1989' has been neglected because it fits badly into modernist liberal and post‐socialist interpretations of 1989. Instead, using the global age thesis, '1989' is reinterpreted as a staging post in the emergence of a politics based on the limits and risks of the modern project.